INHBA upregulation correlates with poorer prognosis in patients with esophageal squamous cell carcinoma - Lyu, Shanshan (Cancer Manag Res, 2018)
PURPOSE: INHBA, which encodes a member of the TGF-beta superfamily of proteins, has been identified to play a critical role in different types of cancer. However, its clinical significance in esophageal squamous cell carcinoma (ESCC) has never been reported. PATIENTS AND METHODS: In this study, we collected 239 ESCC paraffin-embedded specimens and measured the expression of INHBA with immunohistochemistry (IHC). The clinical and prognostic significance of INHBA expression was statistically analyzed. What is more, we conducted a meta-analysis to study the prognostic value of INHBA expression in multiple types of solid tumors. RESULTS: The results showed that INHBA expression was observed predominantly in the cytoplasm of cells in the ESCC specimens. INHBA expression was closely correlated with N categories (P=0.026). Kaplan–Meier analysis showed that ESCC patients in the low INHBA expression subgroup had significantly better prognosis than those with high INHBA level. Subgroup analysis revealed that INHBA distinguished the disease-free survival (DFS) and overall survival (OS) when patients were stratified by TNM stage status and N status. Multivariate analysis results suggested that INHBA expression was an independent factor that affected OS (HR =1.679, P=0.022) and DFS (HR =1.715, P=0.017). In the meta-analysis, six papers with 1321 patients were included and patients with high INHBA level had worse prognosis than patients with low INHBA level (HR 2.50, 95% CI 1.75–3.57, P<0.0001). CONCLUSION: High INHBA level predicts poor prognosis in ESCC and other solid tumors. More studies are required to elucidate the role of INHBA and its clinical application in cancer settings.